Un lugar repleto de dioses. Nota preliminar sobre el programa escultórico de la Subestructura II C de Calakmul, Campeche, México - Daniel Salazar Lama (Journal de la Société des Américanistes)
The project “Art that creates places” aims to study the impact of images in the Mayan built environment and the ability of these images to inscribe or materialize a meaning in space by splicing with the connotations and the functional utilities of architectural forms and other environmental elements. In this research note, are presented the first drawings of the Substructure II C sculptural program al Calakmul, and a brief discussion about the scenes’ content is offered. In addition, the possible functioning of images as a whole and their participation in creating a sense of a place are explored.